2018
DOI: 10.1016/j.jclepro.2017.12.147
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of an integrated rooftop greenhouse for food production in cities

Abstract: Vertical farming is emerging as an effective measure to grow food in buildings and can increase food production in urban areas in a more sustainable manner. This study presents a comprehensive environmental assessment of food production in an integrated rooftop greenhouse (i-RTG)-an innovative vertical farm consisting of a rooftop greenhouse connected to a building-and considers rainwater, residual heat (energy), residual air (CO 2) and food from an industrial ecology perspective. This synergistic connection p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 31 publications
6
72
1
Order By: Relevance
“…In terms of crop efficiency, the integrated rooftop greenhouse (T6) enlarges the crop period for summer products (e.g., tomatoes), as the location of the greenhouse on the top of a building and the use of the building's residual heat for the greenhouse ensures viable year-round temperatures for producing the crop without additional energy input [35]. Furthermore, the integrated rooftop greenhouse (T6) employs rainwater harvested on the roof of the building to satisfy the water demand of the crop [29]. Regarding water efficiency, the two aquaponics case studies (T3 and T4) are also an example of a novelty that boosts water efficiency by combining the water flow for two systems, i.e., crop production and aquaculture, thereby decreasing the overall water demand of the two systems [30,50].…”
Section: Delving Into the Most Common Novelties In Uamentioning
confidence: 99%
“…In terms of crop efficiency, the integrated rooftop greenhouse (T6) enlarges the crop period for summer products (e.g., tomatoes), as the location of the greenhouse on the top of a building and the use of the building's residual heat for the greenhouse ensures viable year-round temperatures for producing the crop without additional energy input [35]. Furthermore, the integrated rooftop greenhouse (T6) employs rainwater harvested on the roof of the building to satisfy the water demand of the crop [29]. Regarding water efficiency, the two aquaponics case studies (T3 and T4) are also an example of a novelty that boosts water efficiency by combining the water flow for two systems, i.e., crop production and aquaculture, thereby decreasing the overall water demand of the two systems [30,50].…”
Section: Delving Into the Most Common Novelties In Uamentioning
confidence: 99%
“…To date, most of these studies have focused on the quantification of the environmental impact of urban agriculture case studies, whereas the literature on social and economic sustainability studies is still limited. The quantification of environmental sustainability has been performed for multiple studies, from the system to the national level, paying particular attention to the comparison with conventional food production [15][16][17][18][19][20][21][22]. Life cycle assessment (LCA) and carbon footprint methods have been employed most frequently in these studies.…”
Section: Quantifying the Sustainability Of Ufpmentioning
confidence: 99%
“…The results depended mostly on the type of UFP and the geographical location. Studies in warm climate areas highlighted the efficiency of UFP cases and the potential environmental benefits from minimizing the distance between producers and consumers (i.e., reduced transport, packaging and food losses) [16,17,21,45,50]. On the contrary, studies in mild climate cities found that the UFP typology and the productivity of the system would determine whether UFP has environmental benefits compared to conventional food systems [18,31].…”
Section: Studymentioning
confidence: 99%
“…These existing RTGs are constructed on roofs that are isolated from buildings. However, this kind of RTG can also be integrated (i-RTG) into a building, using the residual hot and cold air supplied by the building to provide an optimum range of temperatures for the crops and even using the greywater or rainwater collected in or on the building for irrigating the crops (Cer on- Palma et al, 2011;Nadal et al, 2017;Pons et al, 2015;Sanjuan-Delm as et al, 2018).…”
Section: Urban Agriculturementioning
confidence: 99%